Clinical and immunological features of chronic ulcerative stomatitis: A systematic review. (17th February 2022) - Schroeder, Franciane Maria Machado; Palma, Victor de Mello; Rados, Pantelis Varvaki; Visioli, Fernanda
Abstract: Chronic ulcerative stomatitis (CUS) is a rare disease of the mucous membranes with characteristics similar to other autoimmune diseases. The aim of this study was to conduct a systematic review of the literature to recover all reported cases of CUS in order to summarize what are the clinical, demographic, microscopic, immunological features of CUS and its therapeutic response to different drugs. A systematic review of the literature was carried out following the statements of preferred reporting items for systematic reviews and meta‐analyses (PRISMA). The searches were performed in the electronic databases PubMed, Scopus, EMBASE, LILACS, Opengrey, and Google scholar. Inclusion criteria were articles or abstracts reporting at least one case with a final diagnosis of CUS. A total of 696 records were identified through databases, and 25 studies were selected reporting 81 cases. CUS affects more females (92%), and a greater number of cases are reported in Caucasian patients (53%). The age of patients ranged from 20 to 86 years with a mean age of 60 years (±13.86), and 15% of cases reported concomitantly skin lesions. The clinical and histopathological characteristics of CUS are very similar to those of oral lichen planus. The direct immunofluorescence (DIF) remains the gold‐standard diagnostic resource and was performed in 69 cases, revealing a dotted pattern of deposition of stratified epithelium‐specific antibodies (SES‐ANA). The serum of 38 patients was collected for the performance of the indirect immunofluorescence (IIF), and the use of epithelial substrates such as monkey and guinea pig esophagus often resulted in positive SES‐ANA IgG. Most patients were treated with antimalarials, and the treatment of choice that proved to be effective is hydroxychloroquine (HCQ). This entity must be considered in the differential diagnosis of other autoimmune diseases, as it may be underreported.